Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Assessment of validity for the “language spoken at home” variable in Québec death records: Summary. Language, determinant of health status and of services' quality - Trempe, Normand; Boivin, Marie-Claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

La validité de la variable « Langue d’usage à la maison » du Fichier des décès du Québec : synthèse. La langue, déterminant de l'état de santé et de la qualité des services - Trempe, Normand; Boivin, marie-claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)